Efficacy of Anti-EGFR in Microsatellite Instability Metastatic Colorectal Cancer Depending on Sporadic or Familial Origin. (16th May 2020) - Zaanan, Aziz; Henriques, Julie; Cohen, Romain; Sefrioui, David; Evrard, Camille; de la Fouchardiere, Christelle; Lecomte, Thierry; Aparicio, Thomas; Svrcek, Magali; Taieb, Julien; André, Thierry; Vernerey, Dewi; et al.
Abstract: Anti-epidermal growth factor receptor (EGFR) efficacy in patients with microsatellite instability (MSI) metastatic colorectal cancer (mCRC) according to sporadic vs familial origin is unknown. We retrospectively analyzed 128 patients with MSI mCRC treated with first-line chemotherapy ± anti-EGFR. Among them, 61 and 67 patients were respectively categorized as familial and sporadic based on mismatch repair protein immunostaining, BRAF mutational status, and MLH1 promoter methylation status. We observed that addition of anti-EGFR to chemotherapy was associated with a statistically significant improvement of progression-free survival for familial (median = 5.0 vs 10.2 months, hazard ratio [HR] = 0.47, 95% confidence interval [CI] = 0.23 to 0.94; P = .03) but not for sporadic (median = 4.4 vs 5.4 months, HR = 0.80, 95% CI = 0.39 to 1.60; P = .52) MSI mCRC patients. In multivariate analysis, the survival benefit of adding anti-EGFR to chemotherapy remained statistically significant for familial MSI cases ( P = .04). These findings deserve to be confirmed in a prospective study and could help decision making in MSI mCRC without access or resistant to immunotherapy.